Analysis of global gravitational precursors before some Asian strong earthquakes - Khalilov, E.; Wang, L.; Khalilova, L. (Геофизический журнал, 2019)
The authors consider the gravitational precursors of Mega Earthquakes in Asia and Southeast Asia: Sichuan earthquake, M7.9, May 12, 2008; Andaman Islands earthquake, M7.5, August 10, 2009; Samoa Islands earthquake, M8.1, September 29, 2009; Northern Sumatra earthquake, M7.8, April 06,2010; Tohoku earthquake, M9, March 11, 2011. All gravitational precursors were recorded using of ATROPATENA earthquake prediction stations.